2005
DOI: 10.2174/1381612054367300
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Vascular Complications: Pathophysiology, Biochemical Basis and Potential Therapeutic Strategy

Abstract: Diabetic vascular complication is a leading cause of end-stage renal failure, acquired blindness, a variety of neuropathies and accelerated atherosclerosis, which could account for disabilities and high mortality rates in patients with diabetes. Recent large prospective clinical studies have shown that intensive glucose control reduces effectively microvascular complications among patients with diabetes, and insulin resistance and postprandial hyperglycemia seem to be involved in diabetic macrovascular complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
395
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 410 publications
(410 citation statements)
references
References 208 publications
(230 reference statements)
9
395
2
4
Order By: Relevance
“…RAGE is a signal-transducing receptor for AGE [1]. Therefore, we first examined the effect of telmisartan on RAGE expression in Hep3B cells.…”
Section: Effects Of Telmisartan On Rage Expression In Hep3b Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…RAGE is a signal-transducing receptor for AGE [1]. Therefore, we first examined the effect of telmisartan on RAGE expression in Hep3B cells.…”
Section: Effects Of Telmisartan On Rage Expression In Hep3b Cellsmentioning
confidence: 99%
“…Non-enzymatic modification of proteins by reducing sugars, a process that is also known as the Maillard reaction, progresses at an extremely accelerated rate in diabetes, thus leading to the formation of AGE [1]. Recent understanding of this process has revealed that the receptor system for AGE (RAGE) plays a central role in the pathogenesis of diabetic vascular complications such as cardiovascular disease [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 There is accumulating evidence that interaction of AGE with the receptor for AGE (RAGE) contributes to the development and progression of various age-or diabetes-related disorders, including cardiovascular disease, Alzheimer's disease, osteoporosis, cancer growth and metastasis. [8][9][10][11] Indeed, we, along with others, have previously shown that AGE stimulate growth or migration of pancreatic cancer, lung cancer, malignant melanoma and renal cell carcinoma cells in vitro through the interaction with RAGE. [12][13][14][15] Therefore, the AGE-RAGE axis may be a therapeutic target for slowing the progression of cancers in patients with diabetes.…”
mentioning
confidence: 82%